PEMBERIAN TEKNIK MENYUSUI GUNA PENCEGAHAN TERJADINYA BENDUNGAN ASI PADA IBU NIFAS - Imamah, Nur; Perbawati , Dinar; Pangestuning Tyas, Trisna (Jurnal SADEWA, 2023)
Breastfeeding technique is one of the factors that affect milk production, if the mother's breastfeeding technique is wrong it will cause the mother to be reluctant to breastfeed because of the pain felt when breastfeeding, resulting in imperfect mammary emptying and causing milk retention. The high incidence of ASI dams at the Tempurejo Health Center in Jember Regency reaches 60% so it is necessary to provide education about breastfeeding techniques to prevent breast milk dams from occurring. This type of activity is in the form of socializing the provision of education on breastfeeding techniques in order to prevent breast milk dams from occurring. The place or location of the activity is carried out in the Work Area of the Tempurejo Health Center which will be carried out in early June - late June 2023 with the target of postpartum mothers who experience breast milk. The results of counseling activities have had a good impact, where postpartum mothers can find out the correct breastfeeding technique to overcome breast milk dams.